Assessment And Factors Influencing the Performance Agricultural Extension Workers in Landak District: A Multiple Linear Regression Approach - Lestari, Yuti; Kurniati, Dewi; Fitrianti, Wanti (JSEP (Journal of Social and Agricultural Economics), 2024)
Due to the lack of current agricultural knowledge, increasing the the capacity of agricultural extension workers is considered as necessary . The intension of this research was to analyze the performance of agricultural extension workers and the factors that influenced the performance of agricultural extension workers in Landak District. In this study, the sample were 32 of extension workers was collected using a non-probabilistic sampling technique, the software that has been used was SPSS with multiple linear regression methods. The results showed that the performance of extension workers at the field of study in 2022 with the predicate of work performance score value is 79.45, in accordance with the work performance value set by the Ministry of Agriculture in the good category. The results of multiple linear regression analysis on the performance of extension agents at the research site were significantly or significantly (positively) influenced by a formal education, work experiences of extension workers and the availability of extension facilities and infrastructure provided by the Department of Agriculture, Fisheries and Food Security of Landak Regency to extension workers.